Pediatric pyogenic sacroiliitis and osteomyelitis - Sushant Srinivasan; Carl Miller; Nour Akhras; Alexander R. Blackwood (MDPI AG, 2012)
Pyogenic sacroiliitis for 1-2% of all cases of septic arthritis with less than 200 cases reported in the English literature since the beginning of the twentieth century. Cultures of joint fluid usually grow Staphylococcus aureus. Prognosis is excellent; however, diagnosis may be difficult due to rarity of disease and non-specific signs, symptoms, and physical findings. Magnetic resonance imaging has been found to be the most useful imaging modality in diagnosis. Most reported cases required prolonged antimicrobial therapy of six to nine weeks. Presented here are two children with pyogenic sacroiliitis managed at a tertiary-care, university hospital and review of the literature on this relatively rare diagnosis.